Motivasi dan Kompensasi Finansial Terhadap Semangat Kerja Karyawan dengan Konflik Kerja sebagai Variabel Moderating - Hutagalung, Robbi Afdhalah; Sarah Imelda; Sopi Pentana (Forum Kerjasama Pendidikan Tinggi, 2024)
This study aims to determine the motivation and direct financial compensation on employee morale with work conflict as a Moderate variable at PT. PLN (Persero) UIP Sumbagut. In this study, an associative research type with a quantitative approach is used. The population and sample in this study are employees of PT. PLN (Persero) UIP Sumbagut with a sample of 135 employees. The results of this study show that the variables of Motivation and Financial Compensation have a significant influence on Work Morevole. For the Work Conflict variable which acts as a moderation variable, in this study the Work Conflict variable is Unable to moderate significantly between the Motivation and Financial Compensation for Work Morale variables.